ChemInform Abstract: KOtBu‐Initiated Aryl C—H Iodination: A Powerful Tool for the Synthesis of High Electron Affinity Compounds. Issue 36 (August 2016) - Shi, Qinqin; Zhang, Siyuan; Zhang, Junxiang; Oswald, Victoria F.; Amassian, Aram; Marder, Seth R.; Blakey, Simon B.
Abstract: This efficient protocol for iodination of electron‐deficient heterocycles is proposed to rely on a radical reaction initiated by single electron transfer from tBuOK to pentafluoroiodobenzene.